Asymmetry in mesial root number and morphology in mandibular second molars: a case report - Gurudutt Nayak; Shashit Shetty; Rhitu Shekhar (Korean Academy of Conservative Dentistry, 2014)
Ambiguity in the root morphology of the mandibular second molars is quite common. The most common root canal configuration is 2 roots and 3 canals, nonetheless other possibilities may still exist. The presence of accessory roots is an interesting example of anatomic root variation. While the presence of radix entomolaris or radix paramolaris is regarded as a typical clinical finding of a three-rooted mandibular second permanent molar, the occurrence of an additional mesial root is rather uncommon and represents a possibility of deviation from the regular norms. This case report describes successful endodontic management of a three-rooted mandibular second molar presenting with an unusual accessory mesial root, which was identified with the aid of multiangled radiographs and cone-beam computed tomography imaging. This article also discusses the prevalence, etiology, morphological variations, clinical approach to diagnosis, and significance of supernumerary roots in contemporary clinical dentistry.